If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6p + 32 + -4p = 22 Reorder the terms: 32 + 6p + -4p = 22 Combine like terms: 6p + -4p = 2p 32 + 2p = 22 Solving 32 + 2p = 22 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-32' to each side of the equation. 32 + -32 + 2p = 22 + -32 Combine like terms: 32 + -32 = 0 0 + 2p = 22 + -32 2p = 22 + -32 Combine like terms: 22 + -32 = -10 2p = -10 Divide each side by '2'. p = -5 Simplifying p = -5
| 2d+c+4=0 | | 15x+3=3(5x+1) | | 5(3x+1)=15x | | 5x-6=12(0.75x-0.3)+10 | | 5x-14=16+10x | | x^2-6x+3y+6=0 | | .09x+.12*5=.10(x+5) | | (8w+17)(11w-23)=0 | | u^2+2-30=0 | | 20=2(2w+w-2) | | x^2+26x+27=0 | | 7+4(0.5+3x)=-15 | | 12+8y-7y=25 | | (-8x^2y)(x^9y^8)= | | (-8x^2y)(x^9y^8)=-8x^11y^9 | | 3(x-2)-4=2 | | -10.3=7.5+2v | | -(-1+7x)-6(-7-x)=36 | | 5x-3=4(x+8)-10 | | y^5-5y^2=0 | | 4w=77.2 | | 2(4x+28)=16 | | 3842=12(-8+5f) | | 450=-75p | | (x-2+3i)(x-2-3i)= | | k-8.4=-3.1 | | 24x-4x=12+4x | | 9y-18y=11-(14y+19) | | 9x+.12*5=.10(x+5) | | 4y-3+2y=6y+8-y | | 6x-3+4x=13 | | 4y-3+2y=6y |